Efeitos do gadolínio sobre a reatividade vascular em aorta de ratos - Angeli, Jhuli Keli (2009)
Introduction: Gadolinium (Gd) at a concentration of 3 µM, “in vitro”, efficiently inhibits the activity of NTPDases and thus it is able to block the intracellular and extracellular hydrolysis of ATP and ADP. The hydrolysis of these nucleotides geration of adenosine, a potent vasodilator. Adenosine, an endogenous nucleside, involved in the modulation of various physiological functions including vascular tone. Objective: To investigate whether blocking activity of NTPDases with Gd affects vascular reactivity. Materials and Methods: We used isolated aortic rings of Wistar rats (250 to 290g). Vascular reactivity was analyzed by concentration-response curves to phenylephrine (PHE 10-10 to 10-4 M) in the presence of 3µM Gd, 100 µM L-NAME, 1mM ATP, 50µM 8- SPT, 5 mM TEA, 10µM losartan, enalapril 10µM. The reactivity was also assessed in the absence of endothelium. We also analyzed the response to 1 mM ATP after precontraction with 10-4 M PHE and the role of intracellular and extracellular calcium on the contractile response induced by phenylephrine in the presence of Gd. The activity of NTPDases was measured in aortic rings 75 µM and 100 µM. Data are presented as mean ± SEM. For statistical analysis we used Student t-test for unpaired and 1-way ANOVA followed by the Fisher’s LSD (Protected t-test). Results: Gd increased the maximum response (Rmax., 71.28 ± 2.73 to 101.4 ± 6.40%) and sensitivity, pD2 (6.69 ± 0.10 to 10:14 ± 2.41) and this response abolished with the endothelium removal. The reactivity was increased by treatment with L-NAME. But there was no significant difference between the curves L-NAME and L-NAME Gd and between the curves TEA and TEA + Gd. ATP reduced the Rmax. (Ct, 70.33 ± 3.64 for ATP, 32.16 ± 7.17 %) but did not alter pD2. Rmax. changed between the curves wile ATP and ATP 8-SPT (32.16 ± 7.17 to 36.98 ± 6.15 %) respectively.The effects of enalapril and losartan showed similar results, and the response unchanged in both the pD2 and in Rmax. Among the groups (losartan vs. Gd-Gd and Gd vs Enalapril Gd). Activity of NTPDases (hydrolysis of ATP) was inhibited with 75 µM and 100 µM Gd (hydrolysis of ATP and ADP) in homogenate of aorta. In the analysis of levels of purine no significant increase in adenosine and ADP occurred. However the levels of ATP were shown to be increased between groups ATP (291.75 ± 53.75) nmoles/mL and ATP+Gd (666.25 ± 5.25)nmoles/mL. Conclusions: Results presented in this work show that in conductance vessels such as aorta, Gd increased vascular reactivity to PHE, being endothelium dependent. Moreover, the study proved the efficiency of Gd as an inhibitor of NTPDases. This finding is reinforced by the vasodilator action of ATP is increased after treatment with Gd. The vasoconstrictor effect of Gd could not be associated with either the blockade of NO production, nor the activation of potassium channels and not in inhibiting the production of adenosine. However this action of increased endothelium-dependent vascular reativity, caused by the use of Gd 3µM, involves stimulation of ACE and angiotensin II receptor, AT1.